2014
DOI: 10.1007/s00464-014-3777-2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative functional health status may predict outcomes after elective colorectal surgery for malignancy

Abstract: Functional health status may predict postoperative outcomes after colorectal cancer surgery. A detailed preoperative evaluation, providing an optimization period before surgery if necessary, and increased utilization of laparoscopic technique may improve outcomes after elective colorectal resections for malignancy in patients who are partially or TDN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…We also found that functional status prior to surgery was frequently correlated with cardiac and respiratory complications, and mortality. This is in line with previous studies that have identified preoperative functional health status as an important predictor of outcomes after colorectal surgery, 24 ventral hernia repair, 25 hepatic resections, 26 and infrainguinal bypass surgery. 27 It is also congruent with Scarborough et al's research that studied 30-day postoperative outcomes and found that functionally dependent patients experienced a 75% greater odds of mortality and 51% greater odds of major morbidity than functionally independent patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that functional status prior to surgery was frequently correlated with cardiac and respiratory complications, and mortality. This is in line with previous studies that have identified preoperative functional health status as an important predictor of outcomes after colorectal surgery, 24 ventral hernia repair, 25 hepatic resections, 26 and infrainguinal bypass surgery. 27 It is also congruent with Scarborough et al's research that studied 30-day postoperative outcomes and found that functionally dependent patients experienced a 75% greater odds of mortality and 51% greater odds of major morbidity than functionally independent patients.…”
Section: Discussionsupporting
confidence: 92%
“…These findings correspond with previous research illustrating that among patients who underwent unplanned reintubation, older and more frail patients (as assessed by the mFI) had an increased risk of mortality. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Our finding that preoperative functional impairment is associated with postoperative complications is consistent with findings from small, prospective single-center studies, underscoring the need to implement system-wide efforts. 3,5,11,[36][37][38][39] A larger single-center study assessed 4 BADLs (no IADL) preoperatively, but outcomes were limited to those found in the NSQIP (ie, they did not include geriatric outcomes). 17 We validated an abbreviated 5-item functional status scale proposed by the ACS, NSQIP, and American Geriatrics Society.…”
Section: Discussionmentioning
confidence: 99%
“…Functional status is emerging as a predictor for poor outcomes in a number of surgical populations (22, 23). In cancer patients, functional status is used to determine fitness for chemotherapy (24). The Eastern Cooperative Oncology Group functional status assessment tool (25) is routinely used to determine fitness for chemotherapy, and can be helpful in determining fitness to withstand surgery as well.…”
Section: Discussionmentioning
confidence: 99%